Avaliação da técnica de dupla camada na soldagem TIG considerando a tenacidade e características metalúrgicas de juntas de aço AISI 8630M e ASTM A182 F22 - Brito, Francisco Felipe Gomes (2014)
With the discovery of the pre-salt, Petrobras is increasingly investing in oil explorations in deep water and ultra deep, which requires a large expenditure on research and development in the area of production. Several underwater structures are welded and have dissimilar joints, e.g. in connection of flow lines and risers with rigid flanges present in manifolds and Christmas trees. This equipment are generally protected with galvanic cathode protection, which promotes the release of hydrogen ions on the surface of materials. This adsorbed hydrogen migrates to the joint which region, facilitating the spread of defects, especially the fissure by hydrogen. In general this work has the objective to evaluate the effects of procedure GTAW welding with wire feed cold applied in buttering of AISI 8630M and ASTM A182 F22, considering the use of Post-Weld Heat Treatment (PWHT) in different conditions for welding dissimilar joints, as well as evaluate the metallurgical characteristics and mechanical properties of dissimilar interface of buttering. The materials used were the AISI 8630M and ASTM A182F22, welded with the nickel alloy AWS ERNiCrMo-3 using the GTAW process with cold wire feed. In a first stage were carried Conventional and Modified Higuchi Test, where were raised the parameters for application of the technique of double layer. In the second stage were manufactured dissimilar joints with different buttering techniques, using the parameters approved and disapproved Higuchi tests, as well as the use of PWHT. Then, samples were taken for analysis of the phenomena occurring in dissimilar interface, as well as, metallurgical and mechanical characteristics. It was possible, through the of Conventional and Modified Higuchi Test, determine for Steel AISI 8630M and ASTM A 182 F22 buttering parameters relationships that, without the use of PWHT, resulting in heat affected zone (HAZ) well refined and hardness close indicated by standards. The HAZ AISI 8630M steel and ASTM A182 F22 were composed basically by tempering martensite and bainite, respectively, where it was observed an intense grain refining in the buttery joints with relations adopted in Higuchi tests while a coarse granulation was observed in the joints with disapproved on the same conditions. Fracture tests indicated that, overall, the highest values of stress intensity factor (K) were obtained when the ends of the notch are located inside the HAZ.